La violence physique à l’école secondaire : point de vue des intervenants scolaires sur l’implication parentale - Alicia Sophie Bérubé; Ève Pouliot (Sociétés et Jeunesses en Difficulté)
School-family collaboration and parental involvement are important elements in the problem of physical violence in high school. This qualitative research conducted through semi-structured interviews with eight school intervenants, documents their point of view on parental involvement and associated factors in physical violence situations. The results highlight the influence of parental involvement in violent behaviors among teenagers. The study indicates importance of a parental support in physical violence and the importance of these actors in resolving the problem. It would be relevant for future studies to look into parental experiences in order to better understand their needs and support them in their parenting role that influence their teens’ behavior in high school.